The Influence of ESG Ratings on Corporate Debt Costs and Debt Ratios : Evidence from Nordic Markets - Pöyhönen, Eero Ara Aapeli (My University, 2024)
The purpose of the thesis is to study how the ESG rating and its individual pillars (Environ-mental, Social, Governance) affect corporate debt costs in the Nordic countries between 2017 and 2023. The theoretical framework of the study is based on stakeholder theory, which emphasizes the responsibilities of companies towards their stakeholders and the impact of these responsibilities on the company's operations and financial performance. The thesis also examines the development of corporate social responsibility (CSR) and the role of ESG in today's financial markets. The literature review focuses on previous studies that have examined the connection be-tween ESG and the cost of debt. These studies have generally found that higher ESG scores can lead to lower debt costs by reducing the risk faced by companies and improving their reputation in the eyes of investors and lenders. The paper also aims to highlight the impact of ESG on the debt ratio of companies, i.e., the proportion of a company's financing that is debt-financed relative to equity. The empirical analysis is based on a panel data set of 2009 Nordic companies and the paper used the Standard Error Pooled Regression method. The results show that ESG rating has no significant effect on the cost of debt of a firm in the Nordic countries in this dataset. Howev-er, the results suggest that companies with a higher social rating can obtain cheaper debt financing. The study also found that ESG can affect a firm's debt ratio, but that this effect also varies significantly across firms. The results of the study highlight the need for further re-search to examine the impact of ESG, particularly in the Nordic countries, where companies generally have high standards of corporate responsibility.

Tutkielman tarkoituksena on tutkia, miten ESG-luokitus ja sen yksittäiset pilarit (Environmen-tal, Social, Governance) vaikuttavat yritysten velkakustannuksiin Pohjoismaissa vuosina 2017–2023. Tutkimuksen teoreettinen viitekehys perustuu sidosryhmäteoriaan, joka koros-taa yritysten vastuuta sidosryhmiään kohtaan ja näiden vastuiden vaikutusta yrityksen toi-mintaan ja taloudelliseen suorituskykyyn. Tutkielmassa tarkastellaan myös yritysten yhteis-kuntavastuun (CSR) kehitystä ja ESG:n roolia nykypäivän rahoitusmarkkinoilla. Kirjallisuuskatsauksessa keskitytään aiempiin tutkimuksiin, jotka ovat tarkastelleet ESG ja velkakustannusten välistä yhteyttä. Aiemmat tutkimukset ovat yleisesti osoittaneet, että korkeammat ESG-pisteet voivat johtaa alhaisempiin velkakustannuksiin, koska ne vähentävät yritysten kohtaamaa riskiä ja parantavat niiden mainetta sijoittajien ja lainanantajien silmissä. Tämä tutkielma pyrkii myös selvittämään, miten ESG vaikuttaa yritysten velkasuhteeseen eli siihen, kuinka suuri osuus yrityksen rahoituksesta on velkarahoitusta suhteessa omaan pää-omaan. Empiirinen analyysi perustuu paneeliaineistoon, joka koostuu 2009 pohjoismaisesta yrityk-sestä, ja tutkimuksessa käytettiin Standard Error Pooled Regression -menetelmää. Tulokset osoittavat, että ESG-luokituksella ei ole merkittävää vaikutusta yrityksen velkakustannuksiin Pohjoismaissa tässä aineistossa. Tulokset viittaavat siihen, että yritykset, joilla on korkeampi sosiaalinen luokitus voivat saada edullisempaa velkarahoitusta. Tutkimuksessa havaittiin myös, että ESG voi vaikuttaa yrityksen velkasuhteeseen, mutta tämä vaikutus vaihtelee mer-kittävästi eri yritysten välillä. Tutkimuksen tulokset korostavat tarvetta jatkotutkimukselle, joka keskittyy ESG:n vaikutusten tarkempaan tarkasteluun, erityisesti Pohjoismaissa, joissa yrityksillä on yleensä korkeat yhteiskuntavastuustandardit.
Keywords: fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance